Are we architects of our own happiness? The importance of family background for well-being - Daniel D. Schnitzlein; Christoph Wunder (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper analyzes whether individuals have equal opportunity to achieve happiness (or wellbeing). We estimate sibling correlations and intergenerational correlations in self-reported life satisfaction, satisfaction with household income, job satisfaction, and satisfaction with health. We find high sibling correlations for all measures of well-being. The results suggest that family background explains, on average, between 30% and 60% of the inequality in permanent wellbeing. The influence is smaller when the siblings' psychological and geographical distance from their parental home is larger. Results from intergenerational correlations suggest that parental characteristics are considerably less important than family and community factors.
Keywords: D3; I31; J62; 330; subjective well-being; family background; intergenerational mobility; siblings